(3CSeGA GdVYaGA hGdhGVYjf hPcQ ef LQMge ef GdCFeI GdcHGQ GdMGaXjfs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s ((3eMi GdOjf Gdfhhi s)
(3ChdgG (B:s
(3GNHQfG GdTjN GHh GdMLGL jhSa Hf Ndjd Hf YHO Gddg GdOeTbi bQGg Ydjg HMdH GfG GHh GdaQL Hf GdLhRi bGd GdMeO ddg GdPi bOQ GdGYhLGL s
(3BNQgG (B:s
(3BNQ MQa GdYjf , jJdhg ai MQa GdZjf ef GSeg ZGdH s
(3gfGc Tc ai fGSN GdeNWhWs
(3LGA ai GdcJGH ef LQMge ef GdCFeI GdcHGQ eKd CMeO Hf MfHd GdHNGQi heSde hZjQge hbO GNJUQg hQJHge Ydi MQha GdeYLe Ke QJHge ai CfaSge Ydi GdMQha CjVlGhajg RjGOGJ ddMGaX GdfGbO eMeO YHO GdhGMO CHj YHOGddg VjGA GdOjf GdebOSis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B500 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B15 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs